2018
DOI: 10.1371/journal.pone.0207542
|View full text |Cite
|
Sign up to set email alerts
|

Three months of slackline training elicit only task-specific improvements in balance performance

Abstract: Slackline training is a challenging and motivating type of balance training, with potential usefulness for fall prevention and balance rehabilitation. However, short-term slackline training seems to elicit mostly task-specific performance improvements, reducing its potential for general fall prevention programs. It was tested whether a longer duration slackline training (three months, 2 sessions per week) would induce a transfer to untrained tasks. Balance performance was tested pre and post slackline training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
3
25
0
1
Order By: Relevance
“…In addition to the lacking effect on the learning rate during the acquisition of a novel task, no direct transfer to the untrained tasks was observed when comparing the first ten trials after the training between groups. This result is in line with previous training studies that were designed to assess the effect of balance training on untrained balance tasks, and found large effects only in the tasks that had been trained [710, 12, 14], underpinning the task-specificity principle of balance training. The task-specificity effect observed here can be explained by the task-specific neural adaptations following balance training [26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to the lacking effect on the learning rate during the acquisition of a novel task, no direct transfer to the untrained tasks was observed when comparing the first ten trials after the training between groups. This result is in line with previous training studies that were designed to assess the effect of balance training on untrained balance tasks, and found large effects only in the tasks that had been trained [710, 12, 14], underpinning the task-specificity principle of balance training. The task-specificity effect observed here can be explained by the task-specific neural adaptations following balance training [26].…”
Section: Discussionsupporting
confidence: 91%
“…This effect can be explained, at least partly, by the experimental test-retest paradigm [27]. This effect emphasizes the need for a control group in studies testing the effect of different types of balance training on balance performance [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the mechanisms might be behind the observed task-specific modulation of the H-reflex, these changes might be important because they can determine early consolidation mechanisms (Muellbacher et al 2002), as well as interference and reconsolidations effects (Walker et al 2003). This short-term task specific adaptation may also explain the previously observed task-specific change in balance performance and the lack of performance transfer to an untrained balance task (Giboin et al 2015(Giboin et al , 2018Giboin et al 2019a, b) that was accompanied by task-specific H-reflex modulation after 6 weeks of training (Giboin et al 2019c). It should be noted that the present results do not preclude the existence of long-term general spinal adaptations, such as that observed in ballet dancers or power-trained athletes (Casabona et al 1990;Nielsen et al 1993).…”
Section: Discussionmentioning
confidence: 94%
“…As ankle control is crucial for successfully executing ballet specific positions and it could be impaired in ankle sprains, a position specific testing with closed eyes is needed. Moreover, some studies showed that athletic and sport training is task specific and skills acquired in a specific task did not completely translate to the same skills in different tasks [29][30][31]. Recently, Thalassinos et al discovered that there were many sport skill-specific bias about sensory inputs for spatial orientation and postural control between experienced soccer athletes, ballet dancers, and nonathletes [32].…”
Section: Introductionmentioning
confidence: 99%